Sustainability analysis of the strengthening processes of a rural association: Asomora a case study - Rodríguez E., Holmes; Ramírez G., Carlos Julián (Revista de Ciencias Agrícolas, 2016)
In Colombia, different public policies have been implemented to support small rural producers as a strategy to improve their access to markets showing low satisfactory results. The aim of this paper was to identify the factors related to the achievement of the sustainability of the strengthening processes of the rural associativity. A qualitative research was carried out with the case study of the Association of Small Producers of Blackberry (Asomora), in the municipality of Trujillo, state of Valle del Cauca. The strengthening process of Asomora showed as the most significant achievement the increase in the direct market-access rate. However, the process did not reach the sustainability of the Association due to self-interest issues, low commitment of the produces to the Association and lack of financial funds to compete with intermediaries. The results of this study showed that to reach sustainability in rural associativity processes, economic, technical, environmental, social and political factors must be integrally and simultaneously analyzed to guarantee the proper construction of social capital through confidence relations between the associations’ members and their commitment to build participative plans.